Analisis Pengaruh Posisi Dinding Geser Terhadap Kapasitas Seismik Struktur Gedung Beton Bertulang Dengan Metode Analisis Pushover - Hidayat, Muhammad; Abdurrasyid, Yunus; Maidiawati, Maidiawati (Jurnal Bangunan, Konstruksi & Desain, 2025)
Indonesia is an earthquake-prone area, so a building structure capable of resisting lateral loads effectively is required. This study aims to analyze the effect of shear wall position on the seismic capacity of reinforced concrete building structures. The research method uses non-linear static analysis (pushover) using SAP2000 software with four model variations: Model 1 without shear walls, Models 2 and 3 with shear walls parallel to the Y axis, and Model 4 with shear walls installed diagonally at two corners of the structure parallel to the X and Y axes. The results show that the addition of shear walls significantly reduces inter-story drift by up to 71.52% and significantly increases the structural capacity. Model 1 (without shear wall) has a basic capacity of 17,886.10 kN (X direction) and 17,597.82 kN (Y direction), while Model 4 (with diagonal shear wall) shows the highest capacity of 41,074.77 kN (X direction) and 29,242.09 kN (Y direction), with an increase of 229.64% in the X direction and 66.18% in the Y direction, making it the most effective configuration among the three models with shear wall. The configuration in Model 4 produces a balanced stiffness distribution in both main directions, with relatively uniform spectral acceleration (Sa) values ​​in the X (0.57 g) and Y (0.51 g) directions. Based on the ATC-40 performance analysis, Model 1 reaches the Damage Control (DC) level indicating that the structure is still considered safe with maintained stability, while Model 4 reaches the Immediate Occupancy (IO) level, indicating a significant performance improvement. Based on the research results, the placement of shear walls diagonally at two corners of the structure (parallel to the X and Y axes) as in Model 4 can increase the stiffness and capacity of the structure, and also improve the level of seismic performance even though it can reduce ductility. The Model 4 configuration is effective in distributing earthquake forces evenly and creating a more balanced structural system compared to other models.